The Role of MSDM in Achieving Company Competitive Advantage - Haryadi, Imam; Bahiroh, Eloh (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
The rapid development of information and technology requires companies to be able to compete in a competitive business environment. This study aims to determine the role of MSDM in achieving a company's competitive advantage. Using qualitative writing techniques and literature reviews, this scientific journal was written by analyzing the relationship between the impact of variables sourced from books and online journals such as Google Scholar, Google Books, and Potral Garuda. MSDM plays a very important role in managing expertise and motivating employees. MSDM has the ability to influence company performance by focusing on developing human resource assets. This is seen as a resource that can provide competitive advantage. By managing employee expertise and motivation, companies can achieve higher levels of performance.